(Invited) Mid-Infrared Colloidal Quantum Dot Based Nanoelectronics and Nano-Optoelectronics. (3rd July 2019) - Hafiz, Shihab Bin; Scimeca, Michael R.; Sahu, Ayaskanta; Ko, Dong-Kyun
Abstract : Electronic and optoelectronic devices fabricated from colloidal quantum dots (CQDs) provide a promising path toward realizing low-cost devices with greatly simplified device fabrication procedure, owing to their solution-processability. The impact that CQD technology would bring is expected to be significant, especially in the mid-infrared application areas, which is currently dominated by epitaxial semiconductor technologies. In this work, we introduce a new generation of infrared CQDs, namely Ag2 Se CQDs, which has been recently uncovered to show distinct optical absorption in the mid-infrared. We report on the fabrication of solution-processed photoconductive photodetectors and discuss our analyses on the electronic and optoelectronic characteristics of our devices. We also demonstrate the feasibility of mid-infrared photodetection with a measured peak responsivity of 0.16 mA/W at 4 μm under room temperature operation.